PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 001 PANGKALAN KASAI KECAMATAN SEBERIDA - Yulihasti, Sri; Alim, Jesi Alexander; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : The purpose of this research to improve science learning result of the fifth grade students at SDN 001 Pangkalan Kasai, Academic year 2014 / 2015. The subject of this research were fifth grade students at SDN 001 Pangkalan Kasai consist of 22 student form of this research was class action research collaborative by using 2 cycles. The data of this research shows that students science learning out comes was increase. In the first cycle the average of teacher activity was 60%, then in second cycle has increase with average 85%. The students activity in the first cycle was 65% and in the second cycle with average 82,5%. The data or this research has increase before teacher did inkuiri learning. The base scor just 6 students (27,27%) increase, the students who pass consist of 13 students (59,09%) in the with average 57,95%, in the cyles 2 increase with students who pass consist of 20 students (90,90%) with average 85,68%, the total increasing was 55,02%. So the hyphotesis in this research can conduded that the application of inkuiri learning can increase the science leraning out comes of the fifth grade students at SDN 001 Pangkalan Kasai can be accepted.Key word : Inkuiri learning science on comes IPA